Elaboración de nuevos criterios para el mejoramiento de la priorización y gestión de pasivos ambientales mineros en el Perú - 2016 - Liñan Paredes, Eduardo Salomón (2017)
This work focuses on research, analyze and propose improvements to the management procedures of mining environmental liabilities according to Peruvian law, with emphasis on the method used for the identification and prioritization of themselves and their environmental risk assessment conducted through six factsheets under the current legislation. For carrying out an appropriate prioritization it is necessary to actually know the degree of environmental risk, which according to this research, should be determined through a proper assessment of quantitative parameters, instead of the current procedure that considers qualitative assessment sheets. That’s why the analysis of water and soil samples from an ex-mining unit or environmental liability was taken as reference, then the results were compared and it was determined whether the resultant environmental risk through the instrumental sampling is comparable to the qualitative assessment currently done by the government. Finally, from the results, criteria and conclusions are suggested to be used as a basis for the implementation of a new system of identification and prioritization which reflects a more accurate reality of the latent environmental risk in the ex-mining units considered as mining environmental liabilities